NCERT Summary (class VI-XII) one liner (Hindi) - Rannjan, Manish (New Delhi Prabhat, 2022)
This book is a summary of NCERT from class vi-xii, which is helpful in various competitive exams like UPSC, UPPSC, BPSC, MPPSC. It consists of History, Geography, Economy, and basic General Knowledge.
Keywords: General Knowledge